Disse index and free fatty acids as markers of insulin resistance and their association with hospital outcomes of coronary bypass surgery in patients with different glycemic status - N. A. Bezdenezhnykh; A. N. Sumin; A. V. Bezdenezhnykh; A. A. Kuzmina; A. V. Tsepokina; А. S. Pervushkina; S. T. Petrosyan; O. L. Barbarash (Сахарный диабет)
AIM: to analyze various indices of insulin resistance and plasma free fatty acid (FFA) levels, and their association with the preoperative status and in-hospital complications after coronary artery bypass grafting (CABG) in normoglycemic patients and patients with carbohydrate metabolism disorders (CMD).MATERIALS AND METHODS: The study included 708 patients who underwent CABG. The glycemic status, preoperative parameters, the specifics of surgical intervention, in-hospital complications were analyzed. The patients were divided into 2 groups: Group 1 (n=266) — patients with CMD (type 2 diabetes mellitus (T2DM) and prediabetes); Group 2 (n=442) — patients without CMD. Plasma FFA and fasting plasma insulin levels were determined, the Disse index, the quantitative insulin sensitivity check index (QUICKI), revised QUICKI were estimated in 383 patients.RESULTS: Screening prior to CABG increased the number of patients with T2DM from 15.2% to 24.1%, prediabetes – from 3.0% to 13.4%, with any CMD – from 18.2% to 37.5%.Patients with CMD showed a higher percentage of significant hospital complications (25.2% vs 17.0%, p=0.007), progression of renal failure (6.3% vs 2.9%, p=0.021), multiple organ failure (4.5% vs 1.7%, p=0.039), sternal wound complications (6.3% vs 2.9%, p=0.018), renal replacement therapy (3.7% vs 1.1%, p=0.020), surgery on peripheral arteries (1.5% vs 0%, p=0.039).According to the results of multivariate analysis, the Disse index turned out to be a significant predictor of the end point (hospital stay >10 days or any significant complication CABG) in several regression models (OR 1.060 in one of the models; 95% CI 1.016–1.105; p=0.006). Independent predictors of the end point were: female gender, age, body mass index, cardiopulmonary bypass duration, left atrium size, left ventricular end diastolic dimension, T2DM, FFA levels (OR 3.335; 95% CI 1.076–10.327; p=0.036), average postoperative glycemia on the 1st day after CABG, failure to achieve the target range of perioperative glycemia.CONCLUSION: Screening for CMD prior to CABG can significantly increase the number of patients with diagnosed CMD. Significant in-hospital complications after CABG tend to be more prevalent in patients with CMD compared with normoglycemic patients. Insulin resistance index Disse, FFA, postoperative glycemia are independent predictors of prolonged hospital stay or postoperative complications of CABG.